Credit Rating Agencies in India: A Study on the Financial Performance: Exploring the Impact of Credit Rating Agencies on Economic Development (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In financial markets for developers, investors and issuers, credit rating agencies (CRAs) play a critical role in growing knowledge asymmetry between various parties. Credit rating lets us understand individuals' credit capabilities in a region. If all of the founders are viewed favorably, so new companies can improve. The country 's income is growing steadily, job prospects are rising, and poverty is lower. When both industries grow so the GDP grows and the economy expands. The paper specifically illustrates the role credit rating agencies play either explicitly or indirectly in a country's growth. The goal is to research the value of credit rating for a developed world.